2021
DOI: 10.1590/1806-93042021000100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of breastfeeding self-effectiveness and its associated factors in puerperal women assisted at a public health system in Brazil

Abstract: Objectives: evaluate breastfeeding self-efficacy and its associated factors in puerperal women assisted at a public health system in Brazil. Methods: it is a cross-sectional analytical study, with convenience sampling and two instruments: sociodemographic, personal and clinical, and Breastfeeding Self-Efficacy Scale (BSES-SF), applied to puerperal women in a puerperal outpatient clinic at two public maternity hospitals in Goiânia/GO, from September to November 2019. Inclusion criteria: mothers in puerperal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
2
0
4
Order By: Relevance
“…Pesquisas vêm demonstrando que, embora possa variar, conforme os contextos social e cultural em que a mulher está inserida, o apoio formal dos profissionais influencia positivamente na iniciação e duração da amamentação, e a ajuda prática parece ser o meio mais efetivo para os profissionais de saúde apoiarem a amamentação. 23 A presença de leitos para as mães dos RNPTs possibilita sua permanência na unidade, favorecendo a oferta de LH para o bebê. Contudo, a quantidade de leitos não foi suficiente para atender todas as mães dos RNPTs, fator que comprometeu a implantação do componente estrutural insumo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pesquisas vêm demonstrando que, embora possa variar, conforme os contextos social e cultural em que a mulher está inserida, o apoio formal dos profissionais influencia positivamente na iniciação e duração da amamentação, e a ajuda prática parece ser o meio mais efetivo para os profissionais de saúde apoiarem a amamentação. 23 A presença de leitos para as mães dos RNPTs possibilita sua permanência na unidade, favorecendo a oferta de LH para o bebê. Contudo, a quantidade de leitos não foi suficiente para atender todas as mães dos RNPTs, fator que comprometeu a implantação do componente estrutural insumo.…”
Section: Discussionunclassified
“…Marketing da indústria de alimentos infantis 8,24 Apoio da família e dos demais membros do grupo social em que a mulher está inserida 8,18 Situação sociodemográfico (classe econômica; educação materna; situação empregatícia da mulher) 8,23,26 Contexto Organizacional Infraestrutura da unidade 11,27 Apoio dos profissionais de saúde na amamentação 8,18 Presença de leite humano, fórmula infantil e fortificante na unidade 21 Aplicabilidade das políticas públicas em prol da amamentação 3,7 Técnicas de extração do Leite Humano 2,8 unidade e retornavam para as suas residências ao final do dia. Cada mãe que autorizou a gravação da entrevista foi identificada com a letra M e o número da entrevista (M1, M2, M3…) para manter o anonimato das participantes.…”
Section: Contexto Externounclassified
“…Research has shown that, although it may vary according to the social and cultural contexts in which the woman is inserted, formal support from professionals positively influences the initiation and duration of breastfeeding, and practical help seems to be the most effective means for health professionals to support breastfeeding. 23 The presence of beds for mothers of PIs enables their permanence in the unit, favoring the provision of LH for the baby. However, the number of beds was not sufficient to meet all mothers of PIs, a factor that compromised the implementation of the structural input component.…”
Section: Discussionmentioning
confidence: 99%
“…Marketing of the baby food industry 8,24 Support from family and other members of the social group in which the woman is inserted 8,18 Sociodemographic situation (economic class; maternal schooling; employment status of the woman 8,23,26 Organizational context Infraestruture unit 11,27 Support from health professionals on breastfeeding 8,18 Presence of human milk, infant formula, and fortifier in the unit 21 Applicability of public policies in favor of breastfeeding 3,7 Human milk extraction techniques 2,8 and returned to their homes at the end of the day. Each mother who authorized the recording of the interview was identified with the letter M and the interview number (M1, M2, M3...) to maintain the participants' anonymity.…”
Section: External Contextmentioning
confidence: 99%
“…Tradicionalmente, o ganho de peso gestacional adequado era entre 9 e 13 kg, independentemente das características da mulher (Ramón-Arbués et al, 2017). Porém, um estudo realizado por Gurgel (2016), relata que depois após o puerpério 15 a 20% das lactantes, ganham 5 quilos, por se tratar do aumento da gordura corporal materna, sendo armazenado durante seis a oito meses após o parto (Fonseca et al 2021;Pinto et al, 2021).…”
Section: Introductionunclassified